Fatal Statin-Induced Rhabdomyolysis by Possible Interaction with Palbociclib - Nelson, Kellie Lynn; Stenehjem, David; Driscoll, Meghan; Gilcrease, Glynn Weldon (Frontiers in Oncology, 2017)
A 63 year old female on prior statin therapy was initiated on palbociclib and fulvestrant for the treatment of metastatic, hormone-receptor positive breast cancer. She subsequently developed sudden progressive muscle weakness that progressed to death within weeks. The patient noticed progressive proximal muscle weakness after two cycles of palbociclib, with no other medication changes in the interim. This rapidly progressed and resulted in death within seven days of presentation to hospital. There has been one previous report of rhabdmyolysis with palbociclib, occurring in a patient on concomitant statin. In this report, we discuss the possible aetiologies of this progressive rhabdomyolysis including time-dependent inhibition of CYP3A4 or inhibition of hepatic uptake transporters, e.g. OATP1B1.